Exposing nursing students to the marketing methods of pharmaceutical companies - SARIKAYA, ÖZLEM (SAGE PUBLICATIONS LTD, 2008)
There is a strong association between reliance on the promotional activities of pharmaceutical companies and a generally less appropriate use of prescription drugs. Pharmaceutical companies direct some of their promotion towards health workers who do not have the authority to prescribe medicines, such as nurses in certain countries. The aim of this study was to determine the impact that exposure to the marketing methods of pharmaceutical companies has on judgments made by nursing students about health worker-pharmaceutical company relationships. A cross-sectional survey was carried out with 442 nursing students in Istanbul, Turkey. The exposure of students to the marketing methods of pharmaceutical companies, whether it be indirectly through observation or directly by first-hand experience, increases the probability that students will adopt rationales that underlie affirmative judgments of health worker-pharmaceutical company relationships. Based on the pervasiveness and ability of drug promotion to influence the perceptions of students, it is imperative that attempts be made to reduce its negative impact.
Keywords: drugs industry; marketing; nursing; nursing ethics; MEDICAL-STUDENTS; NATIONAL-SURVEY; INDUSTRY; PHYSICIANS; PROMOTIONS; ATTITUDES; EXPOSURE; DOCTORS; GIFT; SAY